Pengaruh Kompetensi, Insentif dan Motivasi terhadap Kinerja Pegawai pada Badan Narkotika Nasional Provinsi Kalimantan Tengah - Jalmo Hadi Prayitno; Asriansyah S. Mawung; Achmad Syamsudin (Journal of Environment and Management, 2020)
During the last 2 years (in 2018 and 2019) drug cases in Central Kalimantan Province had increased. As agency in charge of the task, the Provincial National Narcotics Agency (BNNP) of Central Kalimantan, therefore, requires more staffs with specific skills and good performance. The purpose of this study was to determine the effect of competence, incentives and motivation on staffs performance in BNN of Central Kalimantan Province. Primary data were collected from interviews. Secondary data, i.e. the number of BNNP staffs and the number of cases revealed and investigated obtained through media liaison or such as books, notes, evidence that already exists, or archives both published and not published. The respondents were all 37 of Central Kalimantan BNNP staffs. Data were analyzed through validity test, reliability test, hypothesis test, descriptive statistical analysis, inferential analysis, and model evaluation. The results showed that competence and motivation have a significant effect on performance, while the provision of incentives do not have a significant effect on performance.